An "all-in-one" mesh-typed integrated energy unit for both photoelectric conversion and energy storage in uniform electrochemical system. (April 2015) - Shi, Chenglong; Dong, Hui; Zhu, Rui; Li, Heng; Sun, Yichen; Xu, Dongsheng; Zhao, Qing; Yu, Dapeng
Abstract: An "all-in-one" mesh typed integrated energy unit is developed which converts solar energy to electric energy and stores it simultaneously. The entire integrated device operates in uniform electrolyte system which contains 0.8 M Na2 S, 0.8 M S, and 2 M KCl. A double-sided mesh electrode coated with Cu2 S film and carbon nanoparticles is shared by both energy conversion and storage sections. The device we fabricated can realize the co-operation of the energy conversion and storage sections effectively by taking advantages of the mono electrolyte system and the shared double-sided mesh-typed electrode. These properties are beneficial to assembly, miniaturization, and integration of a self-powered system for portable microelectronic devices. Graphical abstract: An "all-in-one" mesh-typed integrated energy unit is developed which converts solar energy to electric energy and stores it. The unique structure of the mesh-typed electrode makes the inner space into a continuous one and the mono electrolyte provides a uniform and homogeneous electrochemical system. These properties are beneficial to assembly, miniaturization, and integration of a self-powered system for portable devices. highlights: The "all-in-one" device can realize energy conversion and storage simultaneously. The unique mesh design allow uniform mono electrolyte throughout the entire device. Double-sided middle electrode is shared by energy conversion and storage sections. The device can realize miniaturization and integration of a self-powered system.